Strategi Revitalisasi Citra Sekolah Berkarakter Melalui Program Eco Islamic School di SD Muhammadiyah Wareng Gunungkidul - Mohamad Joko Susilo; Firmansyah Firmansyah (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2026)
This study focuses on efforts to revitalize the image of a character-based school through the implementation of the Eco Islamic School Program at SD Muhammadiyah Wareng, Gunung kidul. The urgency of this study arises from the declining public trust and decreasing student enrollment, despite the school’s previous reputation for having a strong Islamic identity and character education. This condition calls for a school branding strategy that goes beyond symbolic promotion and is instead grounded in the strengthening of values and authentic educational practices. The study aims to analyze the role of the Eco Islamic School Program as a strategy for revitalizing school image and its relationship with character development and public trust. A descriptive qualitative approach with a literature review method was employed, drawing on scholarly journals, books, and relevant documents. SD Muhammadiyah Wareng was examined as an illustrative context through the use of secondary data, public documents, and media reports to support the conceptual analysis. The findings indicate that the Eco Islamic School Program functions as a new school positioning by integrating Islamic values and environmental awareness into school culture, curriculum, and daily activities. The implementation of this program has the potential to strengthen school identity, rebuild public trust, and enhance the long term positive image and sustainability of the educational institution